The Effect of Prophet Storytelling Therapy on Anxiety Levels in Preschool Children Treated at Inche Abdoel Moeis Regional Hospital, Samarinda - Richa Cahya Setyowati; Ni Wayan Wiwin Asthiningsih; Fatma Zulaikha (Lembaga Pengembangan Kinerja Dosen, 2026)
Hospitalization in preschool children often causes anxiety due to unfamiliar environments, separation from parents, and invasive medical procedures. Unmanaged anxiety may interfere with the healing process and prolong hospitalization. Prophet storytelling therapy is a non-pharmacological intervention that combines distraction and spiritual values ​​to promote comfort and emotional security in children. Methods: This study employed a quantitative pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 16 hospitalized preschool children aged 4–6 years at RSUD Inche Abdoel Moeis Samarinda, selected using purposive sampling. Anxiety levels were measured using the Spence Children's Anxiety Scale (SCAS) Parent Report before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The findings revealed a significant reduction in anxiety levels following the implementation of prophet storytelling therapy. Prior to the intervention, most respondents experienced severe anxiety, whereas after the intervention, the majority showed mild anxiety levels. Statistical analysis Wilcoxon Signed Rank Test indicated a p-value of 0.002 (p < 0.05), confirming a significant difference in anxiety levels before and after the intervention. Conclusion: Prophet storytelling therapy is effective in reducing anxiety levels among hospitalized preschool children. This therapy can be applied as a spiritual-based non-pharmacological nursing intervention to support atraumatic care in pediatric nursing practice.